A finite element formulation for clustered cables with sliding-induced friction. Issue 2 (June 2022) - Bel Hadj Ali, Nizar; Aloui, Omar; Rhode-Barbarigos, Landolf
Clustered (continuous) cables reflect an advantageous solution for reducing the number of tensile elements in engineering systems. During the tensioning or activation of tensile structures, such as cable structures, membranes and tensegrity structures, the deficiency of having to control too many elements can be overcome by employing clustered cables. The use of clustered cables has been shown to alter the structural behavior of tensile systems by modifying the force distribution in the systems. This effect has been showcased under the assumption of frictionless sliding of the cable elements across nodes or pulleys. However, friction can have also impact on the behavior of the system. In this paper, a new Finite Element formulation is proposed for the static analysis of tensile structures with clustered cables. The proposed formulation accommodates sliding-induced friction by the consideration of the Euler-Eytelwein equation as well as geometric nonlinearities. It is found that the sliding-induced friction can significantly modify the force distribution in the system. The applicability and importance of the proposed formulation is demonstrated through the analysis of two examples from the literature.